Global μ-Stability of Complex-Valued Neural Networks with Unbounded Time-Varying Delays - Xiaofeng Chen; Qiankun Song; Xiaohui Liu; Zhenjiang Zhao (Abstract and Applied Analysis)
The complex-valued neural networks with unbounded time-varying delays are considered. By constructing appropriate Lyapunov-Krasovskii functionals, and employing the free weighting matrix method, several delay-dependent criteria for checking the global μ-stability of the addressed complex-valued neural networks are established in linear matrix inequality (LMI), which can be checked numerically using the effective LMI toolbox in MATLAB. Two examples with simulations are given to show the effectiveness and less conservatism of the proposed criteria.